2020
DOI: 10.3389/fonc.2020.01499
|View full text |Cite
|
Sign up to set email alerts
|

S-1–Based Chemoradiotherapy Followed by Consolidation Chemotherapy With S-1 in Elderly Patients With Esophageal Squamous Cell Carcinoma: A Multicenter Phase II Trial

Abstract: Introduction: Intensive treatments can often not be administered to elderly patients with esophageal squamous cell carcinoma (ESCC), leading to a poorer prognosis. This multi-center phase II trial aimed to determine the toxicity profile and efficiency of S-1–based simultaneous integrated boost radiotherapy (SIB-RT) followed by consolidation chemotherapy with S-1 in elderly ESCC patients and to evaluate the usefulness of comprehensive geriatric assessment (CGA). Patients and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…reported that the rate of grade ≥3 toxicities was 50% among 50 elderly EC patients who received definitive radiotherapy ( 23 ). Furthermore, two similar recent studies exploring the efficacy and safety of S-1 based concurrent chemoradiotherapy in elderly EC patients reported high incidence of side effects with 28% of grade 3−4 acute toxicities and 55.4% of grade 3−4 leucocytopenia, respectively ( 24 , 25 ). Zhang et al .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…reported that the rate of grade ≥3 toxicities was 50% among 50 elderly EC patients who received definitive radiotherapy ( 23 ). Furthermore, two similar recent studies exploring the efficacy and safety of S-1 based concurrent chemoradiotherapy in elderly EC patients reported high incidence of side effects with 28% of grade 3−4 acute toxicities and 55.4% of grade 3−4 leucocytopenia, respectively ( 24 , 25 ). Zhang et al .…”
Section: Discussionmentioning
confidence: 92%
“…Recently, two studies published the efficacy of S-1 based chemoradiotherapy in elderly patients with ESCC. The MST were 22.6 and 18.2 months, respectively ( 24 , 25 ). The aformentioned survival data demonstrated that radiotherapy combined with nimotuzumab achieved acceptable therapeutic effects and more importantly with lower toxicities.…”
Section: Discussionmentioning
confidence: 98%
“…RT alone should be recommended with caution even in the eldest group (aged > 85 years). If patients cannot tolerate doublet CT combined with RT, single-drug oral CT drugs can be considered, such as S1, Xeloda, and other uorouracil analogues [12,35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment for elderly patients with esophageal carcinoma appears to be underutilized [9]. Controversies on the selection of the optimal treatment strategy for elderly patients with curable EC, including esophagectomy versus CRT [10,11] or CRT versus radiotherapy (RT) alone, still exist [8,12]. For instance, Abrams JA et al have reported that esophagectomy may be associated with better survival for early-stage EC patients aged ≥ 65 years compared to CRT [11], whereas Koeter M et al have found that survival was comparable among elderly patients (aged ≥ 75 years) with esophageal squamous cell carcinoma (ESCC) who underwent surgery or received de nitive CRT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation